Managerial development model of head of SMA in Padangsidempuan to achieve quality school - Dunia Siagian; Kasuk Rukun; Sufyarma Marsidin; Syafri Anwar (Universitas Riau, 2018)
The aim of this study is to develop a model of leadership managerial competence of head of High School in Padangsidimpuan. The expected model can be used as a reference for school supervisors in conducting guidance of managerial competence of head of SMA Padangsidimpuan. This research was done using research and development (R and D) by applying the procedural model. The data of this research are consisted of (1) qualitative data that was obtained from observation, interview, and documentation of the study and it was analyzed using descriptive statistics. (2) quantitative data by using questionnaire. The qualitative data were analyzed using three ways, ie data reduction, data presentation, and taking conclusions. The findings of this study are (1) The coaching is focused on the administrative aspect and has not yet touched the managerial competence of the principal of SMA Padangsidimpuan and (2) the coaching process has not been done properly. This research resulted a model of managerial competence development for the head of SMA Padangsidimpuan consisting of two components, namely (1) the identification instrument of managerial competence and, (2) the steps of coaching the managerial competence of the principal of SMA Padangsidimpuan. This model is equipped with a support system that includes a program of leadership managerial competence of senior high school Padangsidimpuan. The test results show that this model is practical and effective for use in improving the managerial competence of SMA Padangsidimpuan. How well the model of guiding the managerial competence of the principal produced will not mean anything if its use does not get support from the parties related to the principal guidance in particular and general education management. It is therefore necessary to support the school superintendent to use this model within the Padangsidimpuan.